A Study on BCG Vaccination Using Bifurcated Needle in Babies - Gunardi A.S.; Suyaka Suyaka; L. Ratna Budiarso (Paediatrica Indonesiana, 1979)
Investigation was done on 527 babies comparing BCG vaccination by bifurcated needle and intradermal method. For this study Japanese and Biofarma BCG vaccines were used.